2016
DOI: 10.1126/science.aaf8713
|View full text |Cite
|
Sign up to set email alerts
|

Dirhodium-catalyzed C-H arene amination using hydroxylamines

Abstract: Primary and N-alkyl arylamine motifs are key functional groups in pharmaceuticals, agrochemicals and functional materials as well as in bioactive natural products. However, there is a dearth of generally applicable methods for the direct replacement of aryl hydrogens with –NH2/-NH-alkyl moieties. Here, we present a mild dirhodium-catalyzed C-H amination for conversion of structurally diverse monocyclic and fused aromatics to the corresponding primary and N-alkyl arylamines using either NH2/NHalkyl-O-(sulfonyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
142
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(148 citation statements)
references
References 60 publications
5
142
0
1
Order By: Relevance
“…During the course of studying the substrate scope,w ew ere surprised to observe that the reaction of ortho-methoxy substrate 3 with the NaH-LiI composite provided not only the expected decyanated product 4 (in only 10 %y ield), but also 3H-indole 5 and indoline 6 in 10 %and 57 %yields,respectively (Scheme 3b). Theu se of PMB protection in particular is advantageous since it can be removed readily under transition-metal-free conditions.I t should also be noted that intermolecular amination of the PMB moieties (see Scheme 4b)w as not observed in these intramolecular processes (10,12). We found that with NaH (3 equiv) as abase,addition of LiI or NaI (2 equiv) is crucial to facilitate the substitution.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of studying the substrate scope,w ew ere surprised to observe that the reaction of ortho-methoxy substrate 3 with the NaH-LiI composite provided not only the expected decyanated product 4 (in only 10 %y ield), but also 3H-indole 5 and indoline 6 in 10 %and 57 %yields,respectively (Scheme 3b). Theu se of PMB protection in particular is advantageous since it can be removed readily under transition-metal-free conditions.I t should also be noted that intermolecular amination of the PMB moieties (see Scheme 4b)w as not observed in these intramolecular processes (10,12). We found that with NaH (3 equiv) as abase,addition of LiI or NaI (2 equiv) is crucial to facilitate the substitution.…”
Section: Zuschriftenmentioning
confidence: 99%
“…[3,4] Amination of arenes enables facile construction of benzannulated saturated nitrogen heterocycles,w hich are an omnipresent component of numerous natural alkaloids and potent pharmaceutical. [11,12] However,t hese strategies have been of use for the construction of limited types of nitrogen heterocycles.H erein, we report an unprecedented example of nucleophilic amination of methoxy arenes by atethered amine moiety in the presence of sodium hydride (NaH) and lithium iodide (LiI) (Scheme 2e). On the other hand, ademand for transitionmetal-free procedures arises from the rigid guidelines that limit the level of residual transition-metal contamination in pharmaceutical ingredients.I nt his context, Meyers and coworkers developed am ethod for the intramolecular amination of methoxy arenes,w hich are electrophilically activated by an ortho-oxazoline moiety (Scheme 2b).…”
mentioning
confidence: 99%
“…[2,3] In general, two distinct mechanistic scaffolds can be conceived for functionalization of C À Hb onds:o uter-a nd inner-sphere pathways (Scheme 1a). [5] In the case of C(sp 2 )ÀHf unctionalization, while the intermolecular version of CÀNb ond formation is rarely explored, [6] thei ntramolecular reaction has been widely explored, via putative metal-nitrenoid intermediates,t hus leading to medium-sized (5-to 7-membered) azacycles (Scheme 1a,b ottom left). [5] In the case of C(sp 2 )ÀHf unctionalization, while the intermolecular version of CÀNb ond formation is rarely explored, [6] thei ntramolecular reaction has been widely explored, via putative metal-nitrenoid intermediates,t hus leading to medium-sized (5-to 7-membered) azacycles (Scheme 1a,b ottom left).…”
Section: Heejeong Kim and Sukbok Chang*mentioning
confidence: 99%
“…

Reported herein is the development of rhodiumcatalyzedintramolecular amido transfer as an efficient route to nitrogen-containing macrocycles starting from acetophenone ketoximes tethered with either aryl or alkyla zides.F acile generation of rhodacycles and metal imido intermediates was the key to success in this mechanistic scaffold to represent the first example of an intramolecular inner-sphere C À Ha mination. [5] In the case of C(sp 2 )ÀHf unctionalization, while the intermolecular version of CÀNb ond formation is rarely explored, [6] thei ntramolecular reaction has been widely explored, via putative metal-nitrenoid intermediates,t hus leading to medium-sized (5-to 7-membered) azacycles (Scheme 1a,b ottom left). [1] Fort his reason, efficient and selective catalytic CÀHa mination has been of much interest to researchers.

…”
mentioning
confidence: 99%
“…As the catalytic asymmetric carbometalation reaction of cyclopropenes 1 provides au nique entry to cyclopropylmagnesium species 2,wewere also interested in using this strategy to prepare the challenging enantioenriched cyclopropylamine derivatives 4.Among the available sources for sp 3 -hybridized nitrogen electrophiles to be used in electrophilic amination reactions, [17] we were particularly interested in the reactivity of nitrenoids [18] as well as O-benzoyl hydroxylamine derivatives. [19] Whereas all our efforts at electrophilic amination with nitrenoids failed to produce the expected cyclopropylamine derivatives in decent yields,cyclopropylcopper species, easily obtained from at ransmetalation reaction of 2 with CuCN·2 LiCl in THF,r eacted smoothly with various O-benzoyl hydroxylamines to provide the expected cyclopropylamines 4 in good yields and high enantioselectivity as single diastereomers (Scheme 3).…”
mentioning
confidence: 99%